Analisis Pengadaan Barang dan Jasa Konstruksi Menurut Perpres 70/2012 Terhadap Perpres 4/2015 - Okma yendri; Desi Qomariah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
The construction sector has an important role in economic growth. To realize a condition that all necessary infrastructure that can guarantee an increase in economic activity. Procurement will be infrastructure and infrastructure by the government, using the budget of revenues and expenditures (APBN / APBD). To oversee the use of the budget, must arrange the procurement rules which the regulation amended by Presidential Decree 70/2012 and 4/2015. The tender process is expected to use the electronic media (e-procurement) to be more transparent, accountable, effective and efficient, in line with efforts to eradicate corruption, collusion and nepotism. The research method uses descriptive research. The sampling technique used purposive sampling with data taken from LPSE Musi Rawas and questionnaires to respondents as service providers, service users, and the auction committee. A descriptive analysis of data processing and data processing using a Likert scale questionnaire on the subject of the study variables The results of a comparative analysis of the construction tender based on Presidential Decree 4/2015 is the same as the Presidential Decree 70/2012. It's just that there is a difference in the duration of time the activity evaluation of the Proposal, namely the regulation 70/2012 is 4 days while on the regulation 4/2015 is 11 days. The duration of time on activities Sanggah Auction Results period is 4 days while the Presidential regulation 70/2012 4/2015 is 6 days.